Flat Cap Atomizer Performance in Filtering Welding Fume - Muhammad Faiz Azfar Abu Hassan,; Ts. Dr. Mohammad Farid bin Sies,; Ahmad Fakruaiman Anuar, (Research Progress in Mechanical and Manufacturing Engineering, 2024)
In order to suppress or filter the harmful contaminants contained inside welding fumes, air filters are the essential device. This study focuses on the filter's performance in a local exhaust ventilation system (LEV) by using an internal mixing atomizing nozzle. Experimental work will be carried out to determine the atomizer’s performance according to the correct method and procedure to ensure a valid result and data are achieved. The type of internal mixing atomizing nozzle implemented in this experiment is a Flat Cap Atomizer. The instalment of internal mixing atomizing nozzle to the LEV system creates a difference in the pressure of air inside the ducting system. When the welding process starts, the welding fume will be suck by the LEV system and going through a filter box attached with the atomizer which produces water mist to act as a filter before being released into the environment. At the end of this study, the data collected from experimental works are proved using laboratory testing which is by using the Inductively Coupled Plasma Optical Emission Spectroscopy (ICP-OES) method and were compared to the previous study. The internal mixing atomizing nozzle performance can be said to be the most efficient used for the local exhaust ventilation system (LEV).